Minimum Inhibitory and Fungicidal Concentration Tests Of Snakehead Fish (Channa Striata) Oil Extracts Against Candida Albicans: An In Vitro Study - Nabila; Ade Puspa Sari; Trisnawaty K (Sriwijaya Journal of Dentistry, 2020)
Introduction: Candida albicans (C. Albicans) is an oral cavity commensal organism that can shift into a pathogenic form under certain conditions. Nowadays, natural substances used as an alternative for a new antifungal agent. Snakehead fish oil extracts have been reported to have antifungal effect i.e; unsaturated fatty acids such as Omega-3 and Omega-6. The purpose of this study was to investigate the antifungal activity of snakehead fish oil extracts against C. Albicans. Materials and Methods: An in vitro laboratory study with a posttest control group design was established. To produce the snakehead fish oil extracts, wet rendering method was used. The snakehead fish oil extracts then tested with microdilution method to determine Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) against C. Albicans. An 0,062-32 μl/ml concentrations used for the microdilution test and 2-32 μl/ml for the disc-diffusion test. Nystatin (100 μg/ml) was used as the positive control. Results: There were visible growths and no inhibition zone in all concentrations of snakehead fish oil extracts. Conclusion: 0.062-32 μl/ml concentrations of Snakehead fish oil extracts did not have the abilities to decrease the growth of C. albicans.